Comparative assessment of psychophysical fitness indicators of contemporary students of an economic university with GTO standards - Chen , Jingjing (Theory and Practice of Physical Culture, 2026)
Objective of the study is to assess the compliance of the psychophysical fitness indicators of modern female students of an economic university with the GTO standards. Methods and structure of the study. An assessment of the psychophysical fitness of 40 first-year female students at the Plekhanov Russian University of Economics was conducted. The results of the students’ physical fitness are presented in terms of indicators of coordination, speed and strength, flexibility and joint mobility. Based on the indicators of coordination development, the following conclusions can be made: in the test of the ability to maintain dynamic balance (Romberg test), the students’ results correspond to an unsatisfactory level. Results and conclusions. Analysis of the indicators characterising the ability to maintain dynamic balance also indicates only a satisfactory level of this ability. The data obtained allow us to conclude that the students have reduced vestibular function, which can cause symptoms such as dizziness, balance disorders, nausea and even a tendency to fall, leading to a risk of injury. After analysing the indicators reflecting the mental state of the females, it can also be concluded that the students show signs of tension and low mental activation.